The Dynamics of City Formation. - Henderson, J; Venables, A (National Bureau of Economic Research, Inc., 2008)
This paper examines city formation in a country whose urban population is growing steadily over time, with new cities required to accommodate this growth. In contrast to most of the literature there is immobility of housing and urban infrastructure, and investment in these assets is taken on the basis of forward-looking behavior. In the presence of these fixed assets cities form sequentially, without the population swings in existing cities that arise in current models, but with swings in house rents. Equilibrium city size, absent government, may be larger or smaller than is efficient, depending on how urban externalities vary with population. Efficient formation of cities with internalization of externalities involves local government intervention and borrowing to finance development. The paper explores the institutions required for successful local government intervention.